Classification of reading skills of early childhood with C4.5 algorithm - Suherman Suherman; Agus Nursikuwagus; Ahmad Sugiyarta; Indah Komala (ILKOM Jurnal Ilmiah, 2022)
Early age is a golden age for children, which is important to improve their development. The children also need to get a good education according to development to improve their abilities. The education provided is certainly following the developmental aspects, one of which is language. The language skills needed at this age is early reading skills. In the understanding given by the teacher, it was found the problems and the need related to it. There is no determination of the classification of early childhood reading skills. At this moment, the teacher has difficulty providing the achievement of reading skills to students based on the criteria of early reading ability and classifying it and improving learning quality to each student and material for discussion with parents. There is a suggestion given to achieve the goals and resolve it that the classification of early childhood reading skills has been designed and for data processing is carried out using a computer. This study uses a decision tree and Algorithm C4.5 for the method. Algorithm C4.5 is included in the classification based on Decision Tree, which Algorithm C4.5 is a method that can handle features with numeric types. The purpose of this study is to perform classification using Algorithm C4.5 as a method that can find out the level of reading skills in early childhood, based on the criteria, so that classification can be done easily and get the right improvement suggestion. The result in this study is that the Algorithm C4.5 method has a good result in solving and calculating for the classification so that the accuracy value of the Algorithm C4.5 calculation that has been carried out is 77,14%.